2000
DOI: 10.1104/pp.124.1.331
|View full text |Cite
|
Sign up to set email alerts
|

Mollusc-Algal Chloroplast Endosymbiosis. Photosynthesis, Thylakoid Protein Maintenance, and Chloroplast Gene Expression Continue for Many Months in the Absence of the Algal Nucleus

Abstract: Early in its life cycle, the marine mollusc Elysia chlorotica Gould forms an intracellular endosymbiotic association with chloroplasts of the chromophytic alga Vaucheria litorea C. Agardh. As a result, the dark green sea slug can be sustained in culture solely by photoautotrophic CO 2 fixation for at least 9 months if provided with only light and a source of CO 2 . Here we demonstrate that the sea slug symbiont chloroplasts maintain photosynthetic oxygen evolution and electron transport activity through photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
94
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 40 publications
2
94
0
Order By: Relevance
“…Likewise, animal genomes have never been shown to contain psbO; hence, MSP cannot be made by the sea slug in the absence of HGT. We have previously demonstrated that oxygen evolution is linked to photosynthetic electron transport in the sea slug for at least 5 months after being removed from its algal prey (27), and photosystem II is generally highly susceptible to photo-oxidative damage requiring de novo synthesis and reassembly of its subunits (38,39). For these reasons, we targeted psbO for HGT from V. litorea to E. chlorotica.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, animal genomes have never been shown to contain psbO; hence, MSP cannot be made by the sea slug in the absence of HGT. We have previously demonstrated that oxygen evolution is linked to photosynthetic electron transport in the sea slug for at least 5 months after being removed from its algal prey (27), and photosystem II is generally highly susceptible to photo-oxidative damage requiring de novo synthesis and reassembly of its subunits (38,39). For these reasons, we targeted psbO for HGT from V. litorea to E. chlorotica.…”
Section: Resultsmentioning
confidence: 99%
“…This emerald green sea slug owes its coloring and photosynthetic ability to plastids acquired during herbivorous feeding (24)(25)(26)(27)(28)(29). The plastids do not undergo division in the sea slug and are sequestered intracellularly in cells lining the finely divided digestive diverticula.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 While the plastids remain photosynthetically active they provide an energy supply, and in some cases, the released organic carbon can totally sustain the sea slugs for several months in the absence of an algal food source, 2 giving rise to the issue of whether lateral gene transfer has occurred between eukaryotic alga and animal † Instituto de Productos Naturales y Agrobiología del CSIC. ‡ Smithsonian Tropical Research Institute.…”
mentioning
confidence: 99%